PELAPORAN KEUANGAN DAN PERUBAHAN HARGA - Aulia Asyifa Pane; Nur Syahira; Nurlaila (LPPM STIE YKPN Yogyakarta, 2024)
The study examines the impact of pricing changes on financial reporting in Indonesian manufacturing firms is examined in this study. This study, which employs a qualitative methodology using case studies, discovers that price changes have an impact on reported earnings and asset values. The quality of financial reporting, net income, and asset valuation are all significantly impacted by changes in the price of raw materials. When it comes to handling price volatility, the fair value approach has been shown to be more applicable than the historical approach. Furthermore, openness in reporting boosts investor trust. This study recommends enhancing the accounting system's ability to handle pricing dynamics and implementing adaptive accounting procedures.